2019
DOI: 10.1002/jcb.29060
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MIR155HG facilitates pancreatic cancer progression through negative regulation of miR‐802

Abstract: Long noncoding RNAs (lncRNAs) present the key regulatory functions in tumorigenesis. More and more studies have suggested that lncRNA MIR155HG is involved in different human cancers. However, the underlying regulatory role of lncRNA MIR155HG and potential mechanisms in pancreatic cancer (PC) remain illusive. In this research, our group found that lncRNA MIR155HG expression was remarkably increased in PC tumor tissue and cells compared to that in the adjacent normal tissue and cells. In addition, higher MIR155H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…responses against viral infections [8]. Additionally, MIR155HG has been revealed to function as an oncogene in the progression of diverse cancers, such as pancreatic cancer, glioblastoma and laryngeal squamous cell carcinoma [9][10][11]. In recent, Li et al found MIR155HG regulated M1/M2 macrophage polarization in COPD through regulating interleukins (IL)-1β, IL-10, IL-12 and tumor necrosis factor-α (TNF-α) expression, suggesting that MIR155HG might involve in the development of COPD [12].…”
Section: Introductionmentioning
confidence: 99%
“…responses against viral infections [8]. Additionally, MIR155HG has been revealed to function as an oncogene in the progression of diverse cancers, such as pancreatic cancer, glioblastoma and laryngeal squamous cell carcinoma [9][10][11]. In recent, Li et al found MIR155HG regulated M1/M2 macrophage polarization in COPD through regulating interleukins (IL)-1β, IL-10, IL-12 and tumor necrosis factor-α (TNF-α) expression, suggesting that MIR155HG might involve in the development of COPD [12].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [64] observed that miR-802 not only inhibits the proliferation and invasion but also the epithelial-mesenchymal transition of glioblastoma multiforme cells. miR-802's role has also been described in tongue squamous cell carcinoma [65], pancreatic cancer progression [66], and human cervical cancer [67]. Recently, Zhang et al [68] demonstrated miR-802's ability to inhibit the aggressive behaviors of non-small cell lung cancer cells.…”
Section: Mir-802mentioning
confidence: 99%
“…LncRNAs were discovered in the 1980s and due to their inability to encode proteins, they were previously considered to be ‘transcription noise’ (6). In recent years, an increasing number of studies have indicated that lncRNAs are able to regulate gene expression at the epigenetic, transcriptional and post-transcriptional levels (31). In addition, they are likely to serve a prominent role in the development of cancer (32).…”
Section: Discussionmentioning
confidence: 99%